Use of Pembrolizumab for Treatment of Progressive Multifocal Leukoencephalopathy in People Living with HIV - Carmela Pinnetti; Eleonora Cimini; Alessandra Vergori; Valentina Mazzotta; Germana Grassi; Annalisa Mondi; Federica Forbici; Alessandra Amendola; Susanna Grisetti; Francesco Baldini; Caterina Candela; Rita Casetti; et al. (Viruses, 2022)
Progressive Multifocal Leukoencephalopathy (PML) is a demyelinating disease occurring in advanced HIV infection, caused by the reactivation of poliomavirus JC (JCV). The use of pembrolizumab for treatment is based on the inhibition of programmed cell death protein 1 (PD-1), potentially improving the anti JCV-specific response. We used pembrolizumab with combined antiretroviral treatment (cART) on a compassionate-use basis. At each administration, clinical evaluation, MRI and laboratory testing, including CD3, CD4, CD8, PD-1 markers, HIV-RNA and JCV-DNA in cerebrospinal fluid (CSF)/plasma pairs, were performed. The JCV-specific T cell response was analysed by Elispot assay. This study included five HIV patients: four male, median age 43 years (29–52), median CD4 and CD8 count 150 (15–158) and 973 (354–1250) cell/mm3, respectively; median JCV-DNA and HIV-RNA in CSF/plasma pairs 9.540/1.503 cps/mL and 2.230/619 cp/mL, respectively. Overall, patients received between two and seven doses of pembrolizumab. After treatment, we observed JCV-DNA reduction and PD-1 down-regulation both in CSF and in plasma (high in circulating CD4 and CD8 at baseline), which remained stable at low levels in all patients. Three out of five patients showed stability of clinical picture and neuroimaging, while two others died. More data are needed in order to identify predictors of response to therapy.